4D Printing of Shape Memory Materials for Textiles: Mechanism, Mathematical Modeling, and Challenges. (4th March 2021) - Biswas, Manik Chandra; Chakraborty, Samit; Bhattacharjee, Abhishek; Mohammed, Zaheeruddin
Abstract: Shape memory materials (SMMs) in 3D printing (3DP) technology garnered much attention due to their ability to respond to external stimuli, which direct this technology toward an emerging area of research, "4D printing (4DP) technology." In contrast to classical 3D printed objects, the fourth dimension, time, allows printed objects to undergo significant changes in shape, size, or color when subjected to external stimuli. Highly precise and calibrated 4D materials, which can perform together to achieve robust 4D objects, are in great demand in various fields such as military applications, space suits, robotic systems, apparel, healthcare, sports, etc. This review, for the first time, to the best of the authors' knowledge, focuses on recent advances in SMMs (e.g., polymers, metals, etc.) based wearable smart textiles and fashion goods. This review integrates the basic overview of 3DP technology, fabrication methods, the transition of 3DP to 4DP, the chemistry behind the fundamental working principles of 4D printed objects, materials selection for smart textiles and fashion goods. The central part summarizes the effect of major external stimuli on 4D textile materials followed by the major applications. Lastly, prospects and challenges are discussed, so that future researchers can continue the progress of this technology. Abstract : 4D Printed Textiles: the innovation and revolution in the thread for smart textiles. This review article discusses the convergence of 3DP technology, mathematical modeling, and shape memory behavior of polymers that demonstrates the development of next generation 4D printed multifunctional preforms for textiles and fashion applications. 4D printed textiles can change their shape over time upon external stimulus such as temperature.